Epimeriidae (Crustacea, Amphipoda) from New Zealand with a description of a new species - Lörz, Anne-Nina (Zootaxa, 2008)
Epimeria horsti sp. nov., collected from New Zealand seamounts at 970–1156 m depth, is described in detail. This increases the number of known species of New Zealand Epimeriidae to four. Additionally Epimeria bruuni Barnard, 1961, previously known only from the Kermadec Trench at 2470 m depth, is redescribed using new material collected from Young Nicks Seamount, Hikurangi Plateau. A key is provided for all New Zealand epimeriids. Epimeria horsti can be distinguished from similar species by the unique combination of the following characters: eyes present; dorsal carinae starting on pereon 6; epimera 1–2 posterolateral corner rounded; epimeron 3 posterolateral corner produced.